Strategi Pengelolaan Linen dan Laundry dalam Operasional Pada Samosir Villa Resort Kabupaten Samosir - Sariana Hollandita Prima Putri Daulay; Kiki Maulani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Linen and laundry management is a critical aspect of hotel housekeeping operations because it directly affects cleanliness, guest comfort, service continuity, and operational cost efficiency. Fluctuating occupancy levels require hotels to manage linen availability carefully while maintaining hygiene standards and preventing service disruptions. This study aims to analyze the strategies applied in linen and laundry management, identify operational challenges, and examine managerial efforts to overcome these problems at Samosir Villa Resort, Samosir Regency. This research employed a descriptive qualitative approach with a case study method. Informants were selected through purposive sampling and consisted of a Housekeeping Supervisor and a Room Attendant who were directly involved in linen and laundry activities. Data were collected through semi-structured interviews, observation, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings show that linen and laundry management strategies include the use of personal protective equipment, collection of soiled linen in covered containers, linen sorting before washing, appropriate folding, and hygienic storage of clean linen. Several challenges were found, including laundry delays during high occupancy, machine breakdowns, limited linen stock, and the risk of linen damage caused by improper handling. Managerial efforts include preparing reserve linen, conducting regular staff briefings, improving resource-use efficiency, and planning the procurement of higher-capacity laundry equipment. These findings can serve as an evaluation reference for hotel management in improving linen and laundry effectiveness, supporting smooth hotel operations, and enhancing guest service quality in the future.